Development of Online NAS Application User Guide Website using NextJS 13 and REST API to Enhance User Understanding - Hajjul Ikram; Muhammad Ardiansyah (Jurnal Inotera, 2024)
This research focuses on developing a user guide for the Nusantara Certification Application System (NAS) through an online platform, utilizing NextJS 13 technology and REST API to enhance comprehensive understanding and optimal utilization of NAS features. The implementation of NextJS 13 ensures a responsive and adaptive interface, while the REST API optimizes speed and smooth access to required data. Through a combination of structured video tutorials and information sources in PDF format, the objective of this guide is to provide comprehensive insight into each feature offered within the NAS application. Research findings confirm the success of integrating NextJS 13 technology and REST API, significantly enhancing understanding and efficiency in NAS application use. The primary role of this implementation lies in aiding users to deeply comprehend and optimize the benefits of the NAS application while expediting access to necessary information. In conclusion, the utilization of cutting-edge technology in user guide development has proven to have a positive impact by broadening user insights into the application and enhancing productivity and efficiency in its use. This underscores the significance of employing advanced technology in delivering information to modern application users.